Angular kinematics during top speed sprinting in male intercollegiate track and field and team sport athletes - Clark, K. P.; Meng, C. R.; Walts, C. T.; Ryan, L. J.; Stearne, D. J. (Frontiers in Sports and Active Living, 2025)
In this investigation we examined lower extremity angular kinematics and top speed sprinting performance in 98 male intercollegiate athletes with backgrounds in either track and field (TF, n = 28) or team sports (TS, n = 70). Athletes completed 40 m running trials, with high-speed video recorded from 30-40 m, and 2D sagittal plane motion analysis. Key kinematic variables included: maximum thigh extension and flexion during the swing phase, leg and foot angles of the stance leg at touchdown, swing-leg thigh and knee angles at contralateral touchdown, leg excursion angle during the ground contact phase, thigh total range of motion during the swing phase, and thigh angular velocity and acceleration. Our first hypothesis was that each key kinematic variable would be significantly correlated with top speed both across the entire sample of participants and within groups of TF and TS athletes. Our second hypothesis was that sub-groups of TF and TS athletes of similar top speeds would demonstrate significantly different angular positional strategies. The first hypothesis was partially supported, as each key kinematic variable was significantly correlated with top speed when analyzed across the entire heterogeneous sample (0.30 = |r or Rho| = 0.66, p < 0.05), but most were not significantly correlated when analyzed within groups of TF or TS athletes. The second hypothesis was fully supported, as substantially different angular positions were demonstrated by Slow TF and Fast TS athletes of similar top speeds, with Fast TS athletes typically exhibiting a less front-side and more ground-based strategy compared to their Slow TF counterparts. In contrast to the angular position variables, the physical capacity to rotate the limbs (thigh angular velocity and acceleration) was correlated with top speed both across the entire sample of participants and within groups of TF and TS athletes. Therefore, this study indicates that when coaching and training team sport athletes, more specific kinematic models may be beneficial for technique and performance enhancement during top-speed sprinting.